2019
DOI: 10.1186/s12888-019-2191-7
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for mood and anxiety disorders in older people with intellectual disability in comparison with the general population

Abstract: Background People with intellectual disability (ID) have high prevalence of psychiatric disorders, but even higher rates of prescription of psychotropic drugs. Methods Using Swedish national registers, we identified a group of older people with ID and diagnosis of mood disorders (ICD-10 codes F32-F39) and/or anxiety (ICD-10 code F4) during 2006–2012 ( n = 587) and a referent group of people from the general population with the same diagnoses d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…An Irish study which investigated rates of prescribing of psychotropics in older adults with intellectual disabilities reported no increased risk of antidepressant prescribing or any association with problem behaviours. 32 Several studies have reported the increase in rates of antidepressant prescribing in the general population across the UK, which our findings mirror. [33][34][35] In Scotland the number of antidepressant prescriptions rose from 1.16 to 3.53 million per year between 1992 and 2006, 36 and women were prescribed antidepressants more frequently than men.…”
Section: Principal Findingssupporting
confidence: 82%
See 1 more Smart Citation
“…An Irish study which investigated rates of prescribing of psychotropics in older adults with intellectual disabilities reported no increased risk of antidepressant prescribing or any association with problem behaviours. 32 Several studies have reported the increase in rates of antidepressant prescribing in the general population across the UK, which our findings mirror. [33][34][35] In Scotland the number of antidepressant prescriptions rose from 1.16 to 3.53 million per year between 1992 and 2006, 36 and women were prescribed antidepressants more frequently than men.…”
Section: Principal Findingssupporting
confidence: 82%
“…An Irish study which investigated rates of prescribing of psychotropics in older adults with intellectual disabilities reported no increased risk of antidepressant prescribing or any association with problem behaviours. 32 …”
Section: Discussionmentioning
confidence: 99%
“…The staff has to show understanding, patience, and professionalism in providing health care. Furthermore, research shows that people with ID experience significance healthcare disparities, such as high levels of comorbidities and inappropriate medication prescription, compared to people without ID (Axmon et al, 2019;Bond et al, 2019;Carey et al, 2016;Emerson & Baines, 2011). A qualitative study on people with mild ID and with anxiety and depression described "feelings of broken" in terms of emotional overwhelmed and physically damaged, fear and uncertainty, rendering them unable to detect warning signs and isolated because of their mental health problems (Tomlinson & Hewitt, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Older people with ID are more likely to have inpatient and unplanned visits in psychiatric and somatic healthcare compared to people of similar ages and sex from the general population with affective and anxiety diagnoses (Ahlström et al 2020 ; El Mrayyan et al, 2020 ). In addition, they receive more prescription of medication with increased severity of ID and with the presence of behavioural impairment and with affective and anxiety diagnoses (Axmon et al, 2019 ; McGillivray & McCabe, 2004 ; Tsiouris, 2010 ). Furthermore, older people with ID and psychiatric disorders are more likely to have a broad range of comorbidities, and thus be at risk for inappropriate prescription of medication, and more extended hospitalisations (Bowring et al, 2017 ; O'Dwyer et al, 2016 ; Scheifes et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%